Evaluation of Anti-Aspergillus flavus Activity of Lactic Acid Bacteria Isolated from Vietnamese Fermented Cocoa Beans - Tien Cuong Nguyen; Thi Thao Hoang; Hoang Hiep Nguyen (Microbiology Research, 2025)
The use of biological agents in food preservation is considered a sustainable, modern, and promising approach, in which the use of lactic acid bacteria (LAB) is a potential solution. Additionally, Vietnamese fermented cocoa beans, a naturally diverse microflora, have not yet been assessed for the selection of antifungal LAB. Therefore, this study focused on evaluating the antifungal activities against Aspergillus flavus UBOCC-A-10866 of 19 LAB strains isolated from Vietnamese fermented cocoa beans from the Dak Lak and Dong Nai provinces. The results showed that lactic strains were all capable of inhibiting fungi growth (from 18–99% of the fungal colony diameter after 7 days), of which five LAB strains (L13E48, L7E96, L22E96, L41E96, and L2DN120) were selected due to their great fungi inhibition activities (inhibition rate > 75%). The strain L41E96 (Lactiplantibacillus plantarum) was chosen as the best antifungal species with the minimum inhibitory concentration (MIC) and the minimum fungicidal concentration (MFC) of 0.36 mg/mL.